Serum copeptin as a predictor of risk of hyponatremia after transurethral prostatectomy - Katarzyna Bryc-Walczak; Władysław Bryc; Michał Nowicki (The Korean Society of Nephrology, 2023)
Background Transurethral resection of the prostate gland (TURP) frequently leads to the development of dilutional hyponatremia. Copeptin has been established as a surrogate marker of vasopressin and is measured for clinical assessment of various sodium and water disturbances. This study aims to assess the utility of serum concentration of copeptin and N-terminal prohormone of brain natriuretic peptide (NT-proBNP) for prediction of post-TURP alterations of serum sodium concentration. Methods Forty-three patients with benign prostatic hyperplasia undergoing TURP were enrolled. Serum sodium and copeptin were measured before the procedure, then 12 hours after its completion. NT-proBNP was assessed at baseline. The total amount of fluids and sodium administered intravenously and used to flush the bladder during TURP was calculated in each patient. Receiver operator characteristic (ROC) curve analysis was used to determine value of copeptin and NT-proBNP for prediction of hyponatremia after TURP Results In forward stepwise multiple regression analysis of serum copeptin before surgery and the duration of TURP explained the significant portion of the sodium concentration variation 12 hours from the start of the surgery. ROC curve analysis showed that serum copeptin before surgery predicted development of hyponatremia 12 hours after TURP (area under the curve, 0.775; 95% confidence interval, 0.62-0.89; p < 0.001) with a cut-off point of >78.6 pg/mL with 77% sensitivity and 64.7% specificity. Serum NT-proBNP before surgery did not predict hyponatremia 12 hours after TURP. Conclusion Serum copeptin before TURP surgery, but not NT-proBNP, may be a clinically use-ful marker of the risk of hyponatremia after TURP.